Analisis Perhitungan Metode MOORA dalam Pemilihan Lokasi Kedai Kopi - Hamzah Robbani (Neolectura, 2021)
The purpose of this study was to determine the location of a coffee shop using the MOORA method. The research design used is quantitative with a descriptive approach, namely analyzing one variable to be described without making comparisons and looking for influence with other variables. Data collection techniques carried out by researchers using distance measurements between location choices, land prices, land area, traffic density, and transportation routes. The results showed that the A3 location was the most effective choice for opening a new branch.